THE EFFECT OF VISUAL AND FUNCTIONAL CRITERIA OF PACKAGING: CONSUMER EXPECTATIONS OF ELEMENTS FOR DAIRY PRODUCT PACKAGING - Farahani, Maryam Ghiasabadi; Shababi, Hooman; Ashtiani, Peyman Ghafari (ASEAN Marketing Journal, 2021)
Manuscript type: Research paper Research Aims: This study seeks to investigate the effect of visual and functional criteria on packaging and consumer expectations towards the packaging elements of dairy products for children. Design/methodology/approach: For this purpose a sample containing 334 children between 7- 12 years were used. Sampling method was random sampling and measuring tool was questionnaire. In order to data analysis and hypothesis testing, structured equations test by means of "Lisrel software" was used and the research results show that recyclability of product, easy to carry, packaging (product) form and illustrations on packaging variables haven't positive and significant effect on consumer's expectations toward packaging elements of product. Research Findings: On the other hand packaging (background) color and font style variables have positive and significant effect on consumer's expectations toward packaging elements of product. Thus, according to the results visual criteria have more effective role on packaging than functional criteria. Theoretical Contribution/Originality: As the general rule of all affecting factors in stimulatingVisual and Functional Criteria of Packaging of customers, this is a rare study which investigates and provides insights to clarify the exact role of the factors in the field. Practitioner/Policy Implication: Scrutinizing the motivators of Visual and Functional Criteria of Packaging and their interrelationships would help professionals as well as scholars to understand its determinants, which will lead to more insightful decisions. Further, this understanding may be useful in shaping marketing policies and strategies for Iranian and the other firms al around the world. Research limitation/Implications: Lack of cooperation of some respondents; As well as the limited results to the respondents' perceptions of the questionnaire questions.